Asturiux: detection system of computational anomalies - Corredor, Felipe A.; Villamarin V., Juan D. (Visión electrónica, 2014)
Everyday in network management, it is complex the process to correlate events in different dimensions: legal violation, intrusions, monitoring failures, violation to security policies or breach of standards; to which face professionals, teaching and students in this area in Colombia. This article presents the technological aspects for the design and development of a distributed system for the computational anomalies detection that was termed “Asturiux”, which arises as a product from a research project in the teleinformatics area. To addressing this problematic it use the network security administration, and anomalies detection. The system was fully developed with free software, in which were integrated different technologies for the communication, authentication, persistence, computational intelligence and remote alerts. The verification instruments and the realized tests, reflect a high level of system efficiency, and acceptation from the actors involved.